The relationship between gender role and attitude toward menstruation with female sexual function: A cross-sectional study - Najme Mokhtari; Azadeh Salavati; Elham Azmoude (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Although female sexual function can be affected by many psychological, interpersonal, and sociocultural factors, limited studies have focused on the relationships between this construct with some concepts such as women's attitudes toward menstruation and perception from their gender role. Objective: To investigate the association between gender roles and attitude toward menstruation with sexual function among Iranian reproductive women. Materials and Methods: An observational cross-sectional study was carried out on a group of 164 Iranian women referred to the health centers of Torbat Heydariyeh, between August and December 2018. All eligible women filled the female sexual function index (FSFI), Bem Sex Role Inventory, and Menstrual Attitude Questionnaire. Results: The result showed that the total FSFI score was significantly higher in masculine and androgynous gender role groups than women with undifferentiated gender role (p = 0.014, and p = 0.012, respectively). Nevertheless, androgynous women had better sexual arousal than undifferentiated women (p = 0.013). Significant reverse correlations were observed between the perception of menstruation as a debilitating, bothersome, and predictable event with a total score of FSFI and all subscales except lubrication (p = 0.001). In contrast, there was a positive relationship between denial of any effects of menstruation with total FSFI and all its sub-scores except lubrication (p = 0.001). Conclusion: This study highlighted the role of masculinity and androgyny gender role stereotypes and menstrual attitude in the sexual function of heterosexual women. Future studies are needed to explain how these psychological contexts contribute to different aspects of women's sexuality.